2000
DOI: 10.1039/b001851l
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of pre-irradiated poly(ethylene-alt-tetrafluoroethylene) films with styrene: influence of base polymer film properties and processing parameters

Abstract: The radiation grafting method is of interest for the preparation of ion-exchange membranes for electrochemical and other applications. Typically styrene is used in this method because the grafted polystyrene can be readily modi®ed to introduce a variety of functionalities. The grafting of poly(ethylene-alt-tetra¯uoroethylene), or ETFE, ®lms with styrene by the pre-irradiation method has been investigated and compared to that of poly(tetra¯uorethylene-co-hexa¯uoropropylene), or FEP, and poly(vinylidene ¯uoride)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(109 citation statements)
references
References 20 publications
8
101
0
Order By: Relevance
“…Figure 6 shows the conductivities for the AAEMs as a function of temperature, with the values of at 50 ± 1°C summarized in Table 4 (very undesirable for use as fuel cell fuel/oxidant gas separation and ion-conductive membranes); this limitation is mainly down to the choice FEP base polymer [19].…”
Section: Conductivities Of Aaemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 6 shows the conductivities for the AAEMs as a function of temperature, with the values of at 50 ± 1°C summarized in Table 4 (very undesirable for use as fuel cell fuel/oxidant gas separation and ion-conductive membranes); this limitation is mainly down to the choice FEP base polymer [19].…”
Section: Conductivities Of Aaemsmentioning
confidence: 99%
“…FEP), with subsequent sulfonation to yield PEMs [16,17]. The properties and compositions of the final materials can easily controlled with this methodology [18,19]; radiation-grafted PEMs have been tested in DMFC mode and significantly exhibit lowered in situ methanol permeabilities [20,21]. Radiation-grafted PVDF-based cation-and anion-exchange membranes have also been successfully applied to salt-splitting technologies [22][23][24].…”
Section: )mentioning
confidence: 99%
“…Using Raman-microscopy, it was shown that the grafting of VBC progressed throughout the thickness of the FEP (referred to as graft penetration, see Figure 2 The diffusion coefficient of OH -ions is less than that of protons [52] in nearly all media, so it is essential to maximise IECs to get conductivities as high as possible with AAEMs. It is also essential that the effect of the reaction conditions on the membranes produced is explored in detail for each parent polymer film / monomer combination [62]. Further studies were undertaken at Surrey with these two aims in mind [78]: FEP can be grafted with VBC with degrees of grafting (DOG) of at least 29% (by mass), with the graft penetration improving on increasing DOG; membranes with improved IECs (Cl -forms) of up to 1.1 meq g -1 (cf.…”
Section: Review Of Other Relevant Aaem Systemsmentioning
confidence: 99%
“…A significant proportion of recent fuel cell membrane research involves the radiation-grafting of styrene onto low and high density polyethylene films (LDPE, HDPE), partially fluorinated films such as poly(vinylidene fluoride) (PVDF) and poly(ethylene-co-tetrafluoroethylene) (ETFE), and fully fluorinated poly(tetrafluoroethylene-co-hexafluoropropylene) (FEP) films; subsequent sulfonation yields cation-exchange sites (sulfonic acid groups) [61][62][63][64]. The properties and compositions of the final materials are easily controlled via alteration of the grafting and sulfonation conditions [61,62]. Reviews by Hill et al describes the radiation chemistry of fluoropolymers [65] and the high energy radiation-grafting of monomers onto fluoropolymers [66].…”
Section: Review Of Other Relevant Aaem Systemsmentioning
confidence: 99%
“…Almost all commercially available fluorinated polymers, such as polytetrafluoroethylene (PTFE) [14,15], Teflon-FEP [16,17] fluorinated ethylene propylene copolymer (FEP) [18,19], tetrafluoroethylene perfluoro(propyl vinyl ether) copolymer (PFA) [20,21], poly(vinylidene fluoride) (PVDF) [22,23], ethylenetetrafluoroethylene copolymer (ETFE) [24,25], polychlorotrifluoroethylene (PCTFE) [26], etc., have been reported as being used for radiation-induced grafting with styrene using either simultaneous irradiation or pre-irradiation methods. Irradiation of polymer with ionization radiation produces several other chemical effects such as degradation, crosslinking, and co-polymerization, along with the desired grafting reaction in the presence of monomer [27].…”
Section: Introductionmentioning
confidence: 99%